Vehicle accident management and control system using MQTT - Sudha Senthilkumar; K. Brindha; Shashank Bhandari (Institute of Advanced Engineering and Science, 2020)
The quick development of innovation has made our lives less demanding. Innovation has additionally expanded activity risks and street mishaps occur very often which cause tremendous death toll and damage to property on account of poor response from the people in charge of managing such incidents. The mishap recognition undertaking will give an ideal solution for this problem. An accelerometer or a Tilt Sensor can be used as part of an auto caution application with the goal that unsafe driving can be identified. It can be utilized as a crash or rollover finder of the vehicle amid and after a crash. With signals from a sensor, a serious situation because of an accident can be avoided or attended to at the earliest. At the point of time when a vehicle meets with an accident or an auto moves over, the tilt sensor recognizes the flag and promptly sends it to the microcontroller. The microcontroller sends the alarm message through the IoT Module including the location of the accident through the GPS Module to the police or control group by publishing it over the cloud. So, the crisis enable group can promptly follow the area through the GPS Module, subsequent to receiving and accepting the data. The area can likewise be seen on the Google maps. Vital move can be made if this data reaches the control group in time. This venture is valuable in recognizing the accident with the use of sensors. As a future execution, we can add a remote webcam to the current system in order to capture pictures of the scene of the accident.